The Clinicopathological Features and Prognosis in Patients With Papillary Renal Cell Carcinoma: A Multicenter Retrospective Study in Chinese Population - Hong, Baoan; Hou, Huimin; Chen, Lingxiao; Li, Zhi; Zhang, Zhipeng; Zhao, Qiang; Du, Xin; Li, Yuan; Ye, Xiongjun; Xu, Wanhai; Liu, Ming; Zhang, Ning (Frontiers in Oncology, 2021)
Objective The purpose of this study was to compare the clinicopathological characteristics of type 1 and type 2 papillary renal cell carcinoma (PRCC) and to explore the prognostic factors of PRCC in the Chinese population. Methods A total of 242 patients with PRCC from five Chinese medical centers were retrospectively included. From them, 82 were type 1 PRCC and 160 were type 2 PRCC. Clinicopathological features and oncologic outcomes were reviewed. The Kaplan–Meier analysis and log-rank test were performed to describe the progression-free survival (PFS) and overall survival (OS). Univariate and multivariate Cox proportional hazards regression models were used to analyze the prognostic factors of PRCC. Results Of the 242 patients, the average age at surgery was 55.3 ± 13.1 years. The mean tumor size was 5.1 ± 3.1 cm. Compared with type 1 PRCC patients, type 2 PRCC patients had a larger tumor size and were more likely to undergo radical nephrectomy. Besides, type 2 PRCC patients had higher tumor stage (p < 0.001) and WHO International Society of Urological Pathology (WHO/ISUP) grading (p < 0.001). Furthermore, tumor necrosis was more common in type 2 PRCC than type 1 PRCC (p = 0.030). The Kaplan–Meier survival analysis showed that the PFS and OS of type 1 PRCC patients were significantly better than those of type 2 PRCC patients (p = 0.0032 and p = 0.0385, respectively). Univariate analysis showed that tumor size, surgical procedures, pT stage, WHO/ISUP grading, and microvascular invasion were significant predictors of PFS and OS for type 2 PRCC patients. In the multivariate analysis, only pT stage (p = 0.004) and WHO/ISUP grading (p = 0.010) were the independent risk factors. Among type 2 PRCC patients with pT1 stage, no significant difference was found in PFS and OS between the partial nephrectomy and radical nephrectomy groups (p = 0.159 and p = 0.239, respectively). Conclusion This multi-institutional study reveals the significant differences in clinicopathological variables and oncologic outcomes between type 1 and 2 PRCC. For type 2 PRCC in pT1 stage, the prognosis of partial nephrectomy is not inferior to that of radical nephrectomy, and nephron-sparing surgery can be considered.